Multiple sclerosis: psychological problems (emotional tension, stress, depressive disorders) and accompanying factors - Guty, Edyta; Kozimala, Magdalena; Boratyn, Beata; Mrozowicz, Aneta; Nowak, Przemysław; Balicka-Adamik, Luiza (Journal of Education, Health and Sport, 2019)
Emotional tension, stress and depressive disorders (as a whole referred to as psychological disorders) accompany multiple sclerosis (MS). The aim of this paper has been to determine the frequency of their occurrence and their relation to other disorders common for MS. A group of 67 patients of a neurological clinic in Jarosław and neurological ward in Przemyśl (situated in south-east Poland) were provided with a tailor-made questionnaire. The patients who declared having psychological problems belonged to a group of older adults, who suffered from MS longer and who demonstrated more mobility impairment (higher EDSS score). It was found that the patients experienced also a higher frequency of occurrence of the following: pain (48.8% vs 4.0%), communication difficulties (34.1% vs 0.0%), fatigue syndrome (90.5% vs 13%), sexual dysfunctions (92.7% vs 20.0%). Emotional tension, stress or depressive disorders were found the most common among patients diagnosed with secondary progressive MS (100.0%), and the least common in patients with progressive-relapsing MS (46.9%). Upon combining the respondents’ age, duration of the disease as well as EDSS scores (0.57-0.73), the most significant factor influencing the occurrence of psychological disorders, the authors suggest, was the intensification of mobility impairment.